2009
DOI: 10.1158/1078-0432.ccr-08-1515
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Cytokeratin 20-Positive Circulating Tumor Cells Detected by a Refined Immunomagnetic Enrichment Assay in Colorectal Cancer Patients

Abstract: Purpose: Current immunomagnetic enrichment method can only detect general epithelial antigens of circulating tumor cells (CTC). Further characterization of the CTCs to provide specific information on the tumor type is not possible.We attempted to overcome this drawback by developing the methodology for using a gastrointestinal-specific anti-cytokeratin (CK) 20 antibody to detect CTCs in colorectal cancer patients' blood. Experimental Design: The protocol was validated using a colorectal cancer SW480 cell line.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 26 publications
6
59
0
Order By: Relevance
“…The detected expression in the current study was lower than most of the reported data (9,14) .For instance reported higher expression values of CK20 in colorectal cancer (80%) (9) . Moreover, other studies showed higher frequencies of CK20 in colorectal adenocarcinomas reaching 81% and 84% (17,18) .It's also important to highlight the significance of the reported negative immunohistochemical expression of CK20 in this study (42%) which was associated with higher microsatellite instability in previous studies and thus bad prognosis (19) .…”
supporting
confidence: 50%
“…The detected expression in the current study was lower than most of the reported data (9,14) .For instance reported higher expression values of CK20 in colorectal cancer (80%) (9) . Moreover, other studies showed higher frequencies of CK20 in colorectal adenocarcinomas reaching 81% and 84% (17,18) .It's also important to highlight the significance of the reported negative immunohistochemical expression of CK20 in this study (42%) which was associated with higher microsatellite instability in previous studies and thus bad prognosis (19) .…”
supporting
confidence: 50%
“…These findings provide support to the hypothesis that JAG2 functions to promote metastasis in multiple cancer types. It would be of interest to investigate whether JAG2 is expressed in circulating tumor cells of CRC patients, as these cells have been demonstrated to be associated with tumor-node-metastasis stage and lymph node status (21,22). In addition, the clinical value of JAG2 as a novel biomarker in CRC warrants further study (23).…”
Section: A B Discussionmentioning
confidence: 99%
“…Following inclusion criteria for studies were set: (1) patients diagnosed with non-metastatic colorectal cancer (TNM-stage I-III), (2) CTC detected in peripheral blood samples, (3) pre-and/or postoperative blood samples and (4) samples size of ≥99 patients. Nine studies qualified for further analyses (Table 1) [ [18][19][20][21][22][23][24][25][26].…”
Section: Methodsmentioning
confidence: 99%